Injectable Hydrogel for NIR-II Photo-Thermal Tumor Therapy and Dihydroartemisinin-Mediated Chemodynamic Therapy - Chen, Danyang; Chen, Chuang; Huang, Chunyu; Chen, Tongkai; Liu, Zeming (Frontiers in Chemistry, 2020)
In traditional Chinese medicine, dihydroartemisinin (DHA) is the focus of extensive attention because of its unique activity with Fe2+ to produce reactive oxygen species (ROS) and promote apoptosis. In this work, we designed a newfangled ink@hydrogel containing FeCl3, traditional Chinese ink (Hu Kaiwen ink), and agarose hydrogel to create a synergistic activity with DHA in the treatment of cancer. When the system is irradiated under 1064 nm for a few minutes, the ink in the ink@hydrogel converts the light to heat and hyperthermia causes the reversible hydrolysis of hydrogel. Then, Fe3+ quickly diffuses from the hydrogel to the tumor microenvironment and is reduced to Fe2+ to break the endoperoxide bridge in pre-injected DHA, which results in the release of free radicals for a potent anticancer action. To our knowledge, this is the first report of a hydrogel tumor therapy system that induces a photo-thermal response in the second near infrared window (NIR-II). In vivo experiments also showed a significant effect of DHA-Fe2+ in chemodynamic therapy (CDT) and in photo-thermal therapy. This hydrogel platform provided an encouraging idea for synergistic tumor therapy.